The complexities and synergies of engagement: an ethnographic study of engagement in outpatient pediatric rehabilitation sessions. Issue 16 (31st July 2021) - King, Gillian; Chiarello, Lisa A.; Ideishi, Roger; Ziviani, Jenny; Phoenix, Michelle; McLarnon, Matthew J. W.; Pinto, Madhu; Thompson, Laura; Smart, Eric
Abstract: Purpose: To investigate client (youth/caregiver) and service provider engagement in outpatient pediatric rehabilitation therapy sessions. Methods: In an ethnographic study, five research assistants attended 28 outpatient sessions, mostly delivered by occupational, physical, and speech-language therapists, and rated signs of client, provider, and relational engagement using the Pediatric Rehabilitation Intervention Measure of Engagement – Observation version. Post-session interviews were conducted individually with 13 youth, 15 caregivers, and 26 providers. Results: Overall, there was a moderate to great extent of engagement. Provider engagement was rated as higher than client engagement, particularly in sessions with activities focusing on body structure/function. The interviews indicated associations among engagement-related constructs: (a) expectations influenced engagement/disengagement and therapy progress, (b) engagement was associated with positive affect and relationships, and (c) engagement was strongly associated with relationships and collaboration. Conclusions: Engagement is a central process within a complex system of psychosocial constructs operating in therapy. Engagement is emergent, synergistic, and change-inducing – it emanates from, involves, and influences multiple aspects of therapy. Notably, engagement ties two pivotal elements – positive expectations and positive affect – to positive relationships, collaboration, and therapy progress. Implications for practice include an understanding of how providers manage the therapeutic context and work to foster engagement. Implications for rehabilitation: Engagement, and its various elements, plays a central role in shaping how clients, parents, and clinicians value therapeutic encounters. Optimal therapy is often thought to include engagement, relationships, and collaboration; the importance of therapy expectations, positive affect, and perceptions of progress are frequently overlooked. Engagement and motivation may be maximized when youth and caregivers are asked explicitly about how they view their engagement in therapy. In addition to clarifying and aligning expectations with youth and caregivers, service providers can enhance engagement and motivation by intentionally creating enjoyable and meaningful interactions, developing relationships, negotiating consensus on goals and plans, and demonstrating therapy progress. Service providers can harness engagement and the system of related constructs by listening and communicating effectively, by entering the world of the client and family, and by being aware of, anticipating, and responding to engagement and disengagement.